Benefits of Mediterranean and Japanese Diets among Nurses: A Scoping Literature Review - Vitale, Elsa (Endocrine, Metabolic & Immune Disorders-Drug Targets, 2024)
IntroductionThe present study aimed at all the benefits induced by taking the Mediterranean or Japanese diet among nurses and whether any beneficial differences in intakes between the two diets were considered.MethodsThe author searched PubMed and Embase databases for medical subheadings terms and free full text referring to “Diet,” “Mediterranean,” “Japanese,” and “Nurses” before 31st December 2022.ResultsA total of 14 studies were included in this scoping review, which better underlined all the benefits implicated in the Mediterranean or Japanese diets assumption and also if there were any differences between the two diets. These eating behaviors were exclusively investigated among nurses.ConclusionThe nursing profession has always been considered the most stressful healthcare activity. However, some important concerns in the regular lifestyle, such as eating and physical activity, might help to live better.
Keywords: psychosocial risk factor